Association between mild cognitive impairment and sleep quality in patients with chronic heart failure: a cross-sectional study - Gan, Yanmei; Liao, Tingting; Du, Yao; Liu, Lingfang; Luo, Lan; Huang, Wenhua; Li, Gaoye (Frontiers in Psychiatry, 2025)
ObjectiveMild cognitive impairment (MCI) has increasingly been recognized as a significant comorbidity in patients with chronic heart failure (CHF), adversely affecting prognosis and quality of life, despite limited research examining the role of sleep quality in this relationship. This study aimed to assess the prevalence of MCI and poor sleep quality in patients with CHF and to examine the association between them.MethodsWe conducted a cross-sectional study among 329 patients with CHF recruited from a hospital in Nanning, China, between September 2024 and June 2025. We collected the sociodemographic and clinical characteristics from all participants using a general information questionnaire. We assessed global cognitive function with the Beijing version of the Montreal Cognitive Assessment Scale (MoCA-BJ) and evaluated subjective sleep quality over the preceding one-month period using the Pittsburgh Sleep Scale Index (PSQI). We examined the association between MCI and sleep quality using point-biserial correlation coefficient analysis, and then further assessed it with hierarchical regression models, adjusting for potential confounders.ResultsThe study revealed high prevalence rates of both MCI (58%) and poor sleep quality (70.52%) in the CHF population. A significant positive correlation was identified between MCI and poor sleep quality (r = 0.322, P < 0.01). Multivariable analysis demonstrated that sleep quality remained independently associated with MCI after adjusting for other risk factors, with the final model explaining over half of the variance in MCI risk.ConclusionPoor sleep quality shows a strong independent association with MCI in CHF patients. These findings highlight the importance of sleep assessment in CHF management and suggest that addressing poor sleep quality may represent a valuable approach in comprehensive care strategies aimed at preserving cognitive function in this CHF population.